Evaluating the Impact of Drivetrain Vibrations on MPPT Control Performance in Horizontal Axis Wind Turbines - El Ouali Achraf; Lakhal Yassine; Benchagra Mohamed; Chojaa Hamid; Samagassi Souleymane (E3S Web of Conferences)
This study investigates the impact of drivetrain shift vibrations on the control performance of Horizontal Axis Wind Turbines (HAWTs) using a Proportional-Integral-Derivative (PID) controller for Maximum Power Point Tracking (MPPT). Traditionally, PID controllers are tested on simplified rigid models, which do not account for the complex mechanical vibrations encountered in real-world applications. These vibrations, particularly those caused by drivetrain shifts, can significantly affect the stability and efficiency of the control system. Through detailed simulations involving both rigid and flexible drivetrain models, this paper evaluates how drivetrain vibrations influence the performance of the PID-based MPPT control algorithm. The results indicate that the flexible model, which incorporates drivetrain dynamics, experiences pronounced overshoot, oscillations, and significant drops in power coefficient (Cp) compared to the rigid model. These findings highlight the challenges of maintaining control stability and efficiency under varying vibration conditions, with the flexible model showing compromised stability and reduced power conversion efficiency during certain key intervals. This study emphasizes the importance of considering drivetrain dynamics in wind turbine control system design and provides insights into developing more robust and resilient PID control strategies.